Colonic transit, high-resolution anorectal manometry and MRI defecography study of constipation in Parkinson's disease. (September 2019) - De Pablo-Fernández, Eduardo; Passananti, Valentina; Zárate-López, Natalia; Emmanuel, Anton; Warner, Thomas
Abstract: Introduction: Despite clinical relevance and potential role on the disease pathogenesis, underlying mechanisms of constipation in Parkinson's disease (PD) remain poorly understood. A systematic assessment using complementary physiological investigations was performed to elucidate constipation pathophysiology in order to improve its symptomatic management. Methods: PD patients with constipation were evaluated with clinical questionnaires, colonic transit, high-resolution anorectal manometry and MRI defecography. Results were compared and correlated with clinical features. Results: A total of 42 patients (69% male; age 68 ± 8 years; disease duration 10.5 ± 6.1 years) were included, of whom 33 (78.6%) had objective constipation defined by < 3 bowel movements per week or straining. Severity of constipation measured by self-administered questionnaires correlated with disease severity, burden of motor and non-motor symptoms but not with age, disease duration or Parkinson's medications. Colonic transit and anorectal function (high-resolution anorectal manometry and/or MRI defecography) was assessed in 15 patients. A combination of both delayed colonic transit and anorectal dysfunction was the pattern most commonly found (60% of patients) and overall anorectal dysfunction was more prevalent than isolated slow transit constipation. Physiological findings were heterogeneous including reduced colonic motility, rectal hyposensitivity, defecatory dyssynergia and poor motor rectal function. Conclusion: Subjective constipation in PD is poorly correlated with commonly used definition, assessment questionnaires and physiological results. Multiple complex overlapping pathophysiological mechanisms are responsible including slow transit and anorectal dysfunction. Complementary investigations to assess colonic transit and anorectal function are required in those with refractory symptoms for a systematic assessment and appropriate symptomatic management. Highlights: The underlying pathophysiology of constipation in PD is poorly understood. Colon transit, manometry and defecography showed multiple overlapping abnormalities. Both slow transit and anorectal dysfunction contribute to the symptomatology. Various complementary tests are required for a systematic pathophysiological evaluation. Pathophysiological abnormalities should guide symptomatic management.